2023
DOI: 10.3389/fmars.2023.1042782
|View full text |Cite
|
Sign up to set email alerts
|

Desalination effects on macroalgae (part A): Laboratory-controlled experiments with Dictyota spp. from the Pacific Ocean and Mediterranean Sea

Abstract: Desalination brines from direct seawater intake that get discharged to coastal areas may produce stress responses on benthic marine communities, mostly due to its excess salinity, and especially on sessile organisms; in this context, macroalgae have been understudied in desalination ecotoxicological investigations. In this study, we assessed the short- and long-term cellular tolerance responses in two brown species of the macroalgae genus Dictyota through controlled laboratory conditions. Dictyota kunthii was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Overall, the data obtained in this study point to the presence of a battery of biochemical and molecular biomarkers that represent cellular stress, which can be extrapolated to higher levels of biological organization (e.g., physiology, population). The present study comprehensively described a set of reliable brine-monitoring biomarkers in P. oceanica, and this strategy can be also applied to other habitat-forming organisms in different temperate and tropical latitudes, such as corals (Marques et al, 2023), macroalgae (Muñoz et al, 2023;Rodríguez-Rojas et al, 2020), and other seagrasses (Blanco-Murillo et al, 2023a;Capó et al, 2020). Moreover, compared with previous mesocosmderived data, our results showed that using biomarkers related to osmotic and oxidative stress can provide information on brine-specific responses and also identify other potential combined effects when more stressors are present, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, the data obtained in this study point to the presence of a battery of biochemical and molecular biomarkers that represent cellular stress, which can be extrapolated to higher levels of biological organization (e.g., physiology, population). The present study comprehensively described a set of reliable brine-monitoring biomarkers in P. oceanica, and this strategy can be also applied to other habitat-forming organisms in different temperate and tropical latitudes, such as corals (Marques et al, 2023), macroalgae (Muñoz et al, 2023;Rodríguez-Rojas et al, 2020), and other seagrasses (Blanco-Murillo et al, 2023a;Capó et al, 2020). Moreover, compared with previous mesocosmderived data, our results showed that using biomarkers related to osmotic and oxidative stress can provide information on brine-specific responses and also identify other potential combined effects when more stressors are present, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the field studies have mainly focused on population metrics (e.g., percentage cover, shoot density), shoot morphometry (e.g., growth, foliar surface, necrosis marks), or physiology (e.g., nutrient concentration, carbohydrate content), while information is lacking about the effects of brine-associated hypersalinity at the sub-cellular and metabolic levels (biomarkers) (Roca et al, 2016;Sandoval-Gil et al, 2023;Tsioli et al, 2022). In this regard, the use of experimental transplants may allow the most reliable simulation of natural conditions while modifying the intensity of the studied stressor (Garrote-Moreno, Fernández-Torquemada, et al, 2014;Muñoz et al, 2023;Rodríguez-Rojas et al, 2020). Moreover, it has been demonstrated that the combination of a well-designed field transplantation with the analysis of sub-cellular and metabolic responses is the most effective strategy serving as an early warning tool.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation